The Radio and the Development of Social Skills for Living - Cobo Beltrán, John Kendry (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2015)
The use of radio and intentionally planned in the educational process helps young people acquire a wide range of knowledge related to various academic, scientific and humanistic issues in an interactive and experiential way. On this basis it is possible to infer that the radio is a useful and valuable to consolidate skills for social interaction among students in secondary education resource. That is why the aim of this study is to propose the use of radio as a relevant factor in the assimilation of skills for social life technology resource. To achieve the objective work is part of a descriptive research. The study results show that the incorporation of the radio to the dynamics of educational work is potentially useful in stimulating social skills for living, significantly strengthening emotional and moral skills as equality, respect, collaborative and team work, solidarity, among others, in addition to encouraging students improve their skills in oral and written expression.